2020
DOI: 10.1021/acsami.9b19257
|View full text |Cite
|
Sign up to set email alerts
|

A Metal–Organic-Framework-Derived (Zn0.95Cu0.05)0.6Cd0.4S Solid Solution as Efficient Photocatalyst for Hydrogen Evolution Reaction

Abstract: Photocatalytic water splitting taking the advantage of using solar energy directly is one of the most effective strategies for hydrogen evolution. The development of facile methods for synthesizing highly efficient and stable photocatalysts for hydrogen production still remains a great challenge. Herein, a metal–organic framework (MOF)-templated strategy was designed for the synthesis of solid solutions of (Zn0.95Cu0.05)1–x Cd x S that exhibit outstanding photocatalytic hydrogen production reaction activity. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…In addition, the solution precipitation approach‐synthesized MOFs as a precursor or template to prepare MOFs‐based composites have recently attracted much attention. [ 107,110,111 ] For instance, Chen et al. reported that the Ru‐NH 2 ‐Uio‐66/Mn composites photocatalysts were successfully synthesized by combining one‐step solution precipitation strategy with a solid mixed route.…”
Section: The Synthesis Strategies Of the Mofs And Their Composites‐based Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the solution precipitation approach‐synthesized MOFs as a precursor or template to prepare MOFs‐based composites have recently attracted much attention. [ 107,110,111 ] For instance, Chen et al. reported that the Ru‐NH 2 ‐Uio‐66/Mn composites photocatalysts were successfully synthesized by combining one‐step solution precipitation strategy with a solid mixed route.…”
Section: The Synthesis Strategies Of the Mofs And Their Composites‐based Photocatalystsmentioning
confidence: 99%
“…[ 100–103 ] Benefiting from these merits, many research groups have utilized this approach to synthesize MOFs and their composites as photocatalysts. [ 104–111 ] Several remarkable examples are depicted in the following.…”
Section: The Synthesis Strategies Of the Mofs And Their Composites‐based Photocatalystsmentioning
confidence: 99%
“…Multiple studies have demonstrated that the specific performance and service life of the composites can be controlled via changing the content of mixing metals in the normal MOFs. [81] According to substantial documents, cerium as the most abundant rare earth element is a type of extensively used modifier to be doped into materials to enhance adsorption and removal efficiency. Given this, Liu et al introduced cerium metal into UiO-66-NH 2 to realize the efficient adsorption of phosphate in an aqueous solution (Figure 6a).…”
Section: Mof@metalsmentioning
confidence: 99%
“…[19,20] The bandgapc ould also be finely optimizedb yf acilely changing the molarr atio of different parts of the parent MOFs to improve light-harvesting capability and charge-carrier separation efficiency. [21][22][23][24] Molybdenums ulfide (MoS 2 ), ap -types emiconductor,h as been studied as cocatalyst in semiconductor-based photocatalysts. [25,26] For example, Cu 2 Od ecorated with cocatalyst MoS 2 , synthesized by ao ne-step reaction, showed an HER rate of 600 mmol h À1 g À1 ,w hich is higher than that of bare Cu 2 Ow ith an activity of~300 mmol h À1 g À1 under visiblel ight.…”
Section: Introductionmentioning
confidence: 99%
“…Among the well‐known approaches for the synthesis of nanomaterials, this MOF‐templated approach can endow the derived nanomaterials with high porosity, crystallinity, and importantly, uniformity of the morphology and elemental distribution, which are the keys for efficient separation and transportation of the photoexcited charge carriers . The bandgap could also be finely optimized by facilely changing the molar ratio of different parts of the parent MOFs to improve light‐harvesting capability and charge‐carrier separation efficiency …”
Section: Introductionmentioning
confidence: 99%